Increased sustainability of rice-based systems through use of beneficial rice-microbe associations - CGIAR Research Program on Rice (2019)
In a trial using eight varieties treated with the two rhizospheric microbes, at the 50% N fertilizer rate under continuously flooded conditions, NERICA-L-19, Sahel 108 and Sahel 202 gave above 9 tons/ha with microbe treatment which was significantly higher than their yields without microbe treatment (<8 tons/ha).